1998
DOI: 10.1017/s0016756898001150
|View full text |Cite
|
Sign up to set email alerts
|

Trace elements and Sr and C isotopic signatures in late Neoproterozoic and earliest Cambrian sedimentary organic matter from siliciclastic successions in the East European Platform

Abstract: Sedimentary organic matter deriving from tubes of sabelliditids, vendotaenids, sapropelic films and kerogens was extracted by acid processing from Upper Vendian siliciclastic successions in the East European Platform. Elemental composition obtained by instrumental neutron activation analysis (INAA) displays the increasing cobalt (Co) concentration from 1 ppm at the bottom of Upper Vendian succession to about 800 ppm in the uppermost part near the Precambrian–Cambrian boundary. This distribution is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 42 publications
(27 reference statements)
1
12
0
Order By: Relevance
“…The suggestion that organic matter (organisms) might have absorbed these elements during their life cycle (and preserved after death and fossilization), is being assessed for the time on the basis of analytical data and palaeobiological observations made within a stratigraphically constrained succession. Some authors (Felitsyn et al . 1998) remark that the SOM may have become enriched immediately after death, but before burial, by anaerobic cyanophyte bacteria, though, in the case under study no traces of organic lamina or films were found that could be referred to algae and cyanophytes, unless they occurred indistinctly within the kerogen.…”
Section: Results and Discussion Of Geochemical Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The suggestion that organic matter (organisms) might have absorbed these elements during their life cycle (and preserved after death and fossilization), is being assessed for the time on the basis of analytical data and palaeobiological observations made within a stratigraphically constrained succession. Some authors (Felitsyn et al . 1998) remark that the SOM may have become enriched immediately after death, but before burial, by anaerobic cyanophyte bacteria, though, in the case under study no traces of organic lamina or films were found that could be referred to algae and cyanophytes, unless they occurred indistinctly within the kerogen.…”
Section: Results and Discussion Of Geochemical Datamentioning
confidence: 99%
“…Integrated geochemical and palaeontological approach is frequently adopted for studying stratigraphic successions of major interest, like the bio-radiation in the Neoproterozoic Á Lower Cambrian transition (Bartley et al . 1998;Felitsyn et al . 1998).…”
mentioning
confidence: 99%
“…More details concerning the stratigraphy and composition of the studied successions are presented in numerous publications (e.g. Strauss et al 1997;Felitsyn et al 1998).…”
Section: Geological Settingmentioning
confidence: 99%
“…Thus, unusual preservation of Timan-Pechora molluscs reflects low subsidence temperatures, something that is a general characteristic of the Late Proterozoic -Early Palaeozoic strata of the East European Platform (Felitsyn et al 1998), and minimal tectonic deformation of fossil-bearing strata.…”
Section: Colour Pattern In K Kultavasaensismentioning
confidence: 99%